Procedure for Exporting Wooden Table Furniture to the United States based on Non L/C at PT EASTWIND MANDIRI - Putri, Mafaza Ayudia; Hidayat, Yusmar Ardhi; Nugroho, Jati -; Widyanti, Dika Vivi (Politeknik Negeri Semarang, 2025)
PT Eastwind Mandiri is an exporter of wooden-based furniture. To export their products, they need to prepare the goods, required documents, shipping arrangements, and payment processing after finding a buyer. This project explains the steps involved, starting from finding buyers, preparing the products and documents for export, to managing payments. Several parties are involved in this process, including Customs, Freight Forwarders, Ports, Surveyors, the Department of Industry and Trade, and Banks. The purpose of this research is to analyze the export procedure and payment procedure in exporting wooden table furniture to the United States without using a Letter of Credit (L/C). The research methods include observing the process, conducting interviews, and reviewing related information. This research uses secondary data in the form of documents used for the export of PT Eastwind Mandiri. The study shows that PT Eastwind Mandiri follows all required laws and regulations for exporting, including proper documentation and procedures. The payment method used is CAD (Cash Against Document), where payment is made after the buyer receives the shipping documents. This entire process is summarized in a simple flowchart for clarity